Analysis and Visualization Of Molecular Docking 2hi4 Protein - widiasti, innas (UI Scholars Hub, 2022)
The crystal structure of the human microsomal complex P450 1A2 with alpha-naphthoflavone, a cytochrome P450 (CYP) enzyme is particularly important, as it is abundant in the human liver and alters a more diverse xenobiotic array than any other group of metabolic enzymes. CYP1A2 is abundantly found in the liver and involved in the metabolism of about 10% of clinically used drugs metabolized by CYP enzymes. The current drug discovery and development mostly uses high-throughput screening (HTS). However, this regular method is time-consuming and costly. To address the issue, an advanced drug discovery and development method namely chemical compound database screening through computational methods used in this study as a promising method for chemical compound identification. Molecular docking predicts the conformation and orientation of the ligand in the binding site of the target protein. The results of molecular bonding of 2hi4 protein with 15 chemical compounds showed that three chemical compounds, benzo(a)pyrene, pteryxine, and quinine had satisfactory binding energy levels. A comparison of amino acids seen from 2D visualization shows that there are 7 amino acids in common, namely ALA317, GLY316, ASP313, ASP320, PHE260, PHE226, and THR118.